2020
DOI: 10.1097/cad.0000000000000976
|View full text |Cite
|
Sign up to set email alerts
|

Icaritin inhibits lung cancer-induced osteoclastogenesis by suppressing the expression of IL-6 and TNF-a and through AMPK/mTOR signaling pathway

Abstract: Bone metastasis is one of the common phenomena in the late stage of lung cancer. Inhibition of bone metastasis can improve the survival of lung cancer patients. However, the current drugs for the treatment of bone metastasis have shown little effect on overall survival. Therefore, there is an urgent necessity to identify novel drugs capable of preventing and treating bone metastasis of lung cancer. Our study determined that icaritin (ICT) can inhibit lung cancer-mediated osteoclastogenesis and induce the apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Icaritin is a hydrolysate of icariin, one of the main active components of Epimedium. In recent years, icaritin has been considered as a potential cancer suppressor because of its inhibitory effect on tumors such as lymphoma, lung cancer, and prostate cancer (Wu et al., 2015 , 2020 ; Zhao et al., 2020 ). Wu et al.…”
Section: Resultsmentioning
confidence: 99%
“…Icaritin is a hydrolysate of icariin, one of the main active components of Epimedium. In recent years, icaritin has been considered as a potential cancer suppressor because of its inhibitory effect on tumors such as lymphoma, lung cancer, and prostate cancer (Wu et al., 2015 , 2020 ; Zhao et al., 2020 ). Wu et al.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, metformin can also down-regulate the levels of osteoclastogenesis-related signaling molecules. Activated AMPK can down-regulate C-fos, NFATc1 and NF-κB levels ( Oh et al, 2016 ; Salminen et al, 2019 ; Zhao et al, 2020 ). Both TNF-α and IL-6 (downstream of NF-κB) can positively regulate osteoclast differentiation and function ( Luo et al, 2018 ; Wang and He, 2020 ).…”
Section: Mechanisms Of Metformin Regulation Of the Musculoskeletal Sy...mentioning
confidence: 99%
“…A study has shown that AMP-activated protein kinase (AMPK) plays a negative regulatory role in osteoclast differentiation and function ( Tong et al, 2020 ). Multiple drugs can affect osteoclast differentiation and bone resorption through AMPK-mediated signaling pathways, such as AMPK/NF-κB/ERK, AMPK/mTOR/p70S6K, and AMPK/Nfr2 signaling pathways ( Li Z et al, 2018 ; Tong et al, 2018 ; Peng et al, 2019 ; Zhao et al, 2020 ; Guo et al, 2021 ). Unlike various other drugs whose effects on osteoclast differentiation and bone resorption through AMPK pathway have been widely studied, studies on how ZA affects osteoclasts through the AMPK pathway are relatively recent.…”
Section: Zoledronic Acid Inhibits Osteoclast Differentiationmentioning
confidence: 99%